Perbandingan Efisiensi Antara Pengembangan Dengan Laravel Dan Flutterflow Pada Sistem Informasi Kepegawaian: Studi Kasus: PT XYZ - Riki Chandra; Muhammad Rachmadi (Jurnal Sistem Informasi dan Ilmu Komputer, 2024)
PT XYZ, a building construction and design company in Palembang. The number of employees in this company is 30 employees with project, finance, marketing and also human resources (HR) divisions. PT XYZ has a need to improve the efficiency of human resource management. In the current condition, the company still relies on manual processes for recruitment, attendance, layoff data management, and employee leave applications. This Personnel Information System uses the Rational Unified Process (RUP) method as a system development method. System development uses the Laravel framework, PHP, CSS, HTML programming languages. In the analysis stage using PIECES and Usecase Diagram. System development uses two main approaches, namely using the FlutterFlow low-code platform and the Laravel Framework. The final result obtained is the implementation of a web-based Personnel Information System at PT XYZ. The implementation of this system makes a significant contribution in improving the efficiency and accessibility of staffing data at PT XYZ.